The house at Devil's Neck - Mead, Tom (Mead, Tom. Joseph Spector locked-room mystery, 2025)
"An apparent suicide in a London townhouse uncannily mirrors a similar incident from twenty-five years ago, prompting Scotland Yard's George Flint to delve deep into the past in search of the solution to a long-forgotten mystery. Meanwhile, Joseph Spector travels with a coach party through the rainy English countryside to visit an allegedly haunted house on a lonely island called Devil's Neck. The house, first built by a notorious alchemist and occultist, was later used as a field hospital in the First World War before falling into disrepair. The visitors hold a seance to conjure the spirit of a long-dead soldier. But when a storm floods the narrow causeway connecting Devil's Neck to the mainland, they find themselves stranded in the haunted house. Before long, the guests begin to die one by one, and it seems that the only possible culprit is the phantom soldier. Flint's and Spector's investigations are in fact closely linked, but it is only when the duo are reunited at the storm-lashed Devil's Neck that the truth is finally revealed. Tom Mead once again creates a brilliant homage to John Dickson Carr and the Golden Age of mysteries with this intricately plotted puzzle"--